Pengaruh Latihan Single Leg Bound terhadap Kecepatan Lari 100 Meter - Suhartiwi, Suhartiwi (Universitas Hamzanwadi, 2022)
The purpose of this study was to determine whether there was an effect of single leg bound exercise on the speed of running 100 meters. The population in this study was all class XI students of SMA Negeri 6 Kendari as many as 172 people. The sampling technique in this study used the purposive sampling method, namely the technique of determining the sample under consideration, namely being able to perform a single leg bound movement. Of the 172 people after making the selection who can perform the single leg bound movement, there are 31 people. So the sample in this study amounted to 31 people. The instrument used in this study was a 100 meter run test, then given single leg bound treatment with a volume of 3 times a week for 18 meetings. The research data were analyzed using the normality test, homogeneity test of the data before moving on to the t-test. The results obtained from testing the hypothesis that there is an effect of single leg bound exercise on 100 meter running speed, where t count = 11,426 and significant value 0.000 > = 0.05, then HO is rejected, HI is accepted. From the results obtained, it can be concluded that there is an effect of single leg bound exercise on 100 meter running speed. The contribution of the single leg bound result is 43% and the other 57% is supported by other aspects that are not examined.